KKN-PPM: Pemberdayaan Masyarakat Pengelolaan Sanitasi Air Bersih pada Kawasan Perdesaan Prioritas Nasional di Desa Loeha Kecamatan Towuti - Andi Silfiana; Sugiyanto Sugiyanto; Chrecencya Nirmalarumsari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Real Work Lecture Program-Community Empowerment Learning (KKN-PPM) STIKES Bhakti Pertiwi Luwu Raya Palopo is one of the community service activities carried out routinely by universities. The KKN PPM concept is intended to change the concept of "working for the community" to "working with the community". In addition, to improve its contextualization, KKN-PPM is carried out by changing the development paradigm into an empowerment paradigm. Purpose: The KKN-PPM activities are aimed at empowering and fostering the community to live healthy so that the health status of the village community can be fulfilled. The KKN-PPM implementation program is carried out using two models: the eco-e-development model, and the Center for Environment and Societal model. KKN-PPM activities have produced simple air filters in each hamlet in the village of Loeha with basic materials that can be obtained by residents in the village of Loeha. The incidence of diarrhea decreased or was not included in the list of most diseases in the working area of Bantilang Public Health Center. Increased knowledge and skills of the community about clean water sanitation management technology. It is expected that the level of public health in the village of Loeha can improve. Increase the soul of clean and healthy life, so that they can utilize a larger air source than a clean air source to save community life. The people of Loeha Village are very responsive to this activity, specifically, in making simple clean air filtration, this is evidenced by the considerable number of people present.